Pengaruh Promosi Penjualan dan Shopping Lifestyle terhadap Impulse Buying Produk Fashion - Sarah Fauziah; Rose Rahmidani (Jurnal Ecogen, 2021)
The purpose of this research is to determine the effect of sales promotion and shopping lifestyle on impulse buying of fashion products at Transmart Padang. This is the causative research.The population of the research is Padang city community. The number of research samples as many as 100 people and selected using purposive sampling technique.The data used is the primary data obtained through the distribution of questionnaires to Padang city community with established criteria. The analytical method is multiple regression analysis using SPSS 20.The results indicate that (1) sales promotion and shopping lifestyle advertisements have a significant effect on impulse buying, (2) sales promotion has a significant effect on impulse buying, (3) shopping lifestyles have a significant influence on impulse buyingKeywords : sales promotion, shopping lifestyle and impulse buying